Ab initio protein fold prediction using evolutionary algorithms: Influence of design and control parameters on performance - Djurdjevic, Dusan P.; Biggs, Mark J. (Journal of computational chemistry, 2006)
True ab initio prediction of protein 3D structure requires only the protein primary structure, a physicochemical free energy model, and a search method for identifying the free energy global minimum. Various characteristics of evolutionary algorithms (EAs) mean they are in principle well suited to the latter. Studies to date have been less than encouraging, however. This is because of the limited consideration given to EA design and control parameter issues. A comprehensive study of these issues was, therefore, undertaken for ab initio protein fold prediction using a full atomistic protein model. The performance and optimal control parameter settings of twelve EA designs where first established using a 15‐residue polyalanine molecule—design aspects varied include the encoding alphabet, crossover operator, and replacement strategy. It can be concluded that real encoding and multipoint crossover are superior, while both generational and steady‐state replacement strategies have merits. The scaling between the optimal control parameter settings and polyalanine size was also identified for both generational and steady‐state designs based on real encoding and multipoint crossover. Application of the steady‐state design to met‐enkephalin indicated that these scalings are potentially transferable to real proteins. Comparison of the performance of the steady state design for met‐enkephalin with other ab initio methods indicates that EAs can be competitive provided the correct design and control parameter values are used. © 2006 Wiley Periodicals, Inc. J Comput Chem 27: 1177–1195, 2006